Mycotoxins in grain - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
This leaflet defines mycotoxins, describes food-borne mycotoxins, and provides information on mycotoxin production in food, the prevention of mycotoxins in stored grains and seeds, and the detection of mycotoxins.